Windows Password Vulnerability and Preventive Measures - Patil, Dinesh N.; Meshram, B. B. (Indian Journal of Computer Science, 2016)
With the rise in the use of the Internet, cyber crimes have also increased. One of the most prominent attack that can cause a breach in the security of sensitive system is hacking the password hashes. This paper discusses the window password hashes used in the Windows NT-based operating systems and the loopholes in them. The paper also covers various attacking techniques used by attackers in order to gain access to the password . The experiment carried out to identify and extract the password hashes from the volatile memory is also discussed. Finally the paper suggests mechanism for password protection.